Expansion of Magallana gigas Colonization: Northernmost and Southernmost invasion on Saltmarsh Ecosystems in the SW Atlantic - Molina, Lucas Matías (2023)
This study investigates the colonization of saltmarshes by the invasive species Magallana gigas in the South West Atlantic region. The researchwas conducted in the Bahía Blanca and Río Negro estuaries in Argentina. Oyster densities were assessed in different areas of the saltmarshes.The results show varying densities of M. gigas in different locations, with higher densities observed at the edges of vegetated areas in BahíaBlanca and in non-vegetated areas, particularly saltmarsh channels, in the Río Negro estuary. The mechanisms of oyster arrival and their impacton native species and ecosystem functioning are discussed. This research highlights the need for monitoring and managing invasive species toprotect saltmarsh ecosystems.